2015
DOI: 10.1007/s11266-015-9601-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Volunteer Engagement to Achieve Desirable Outcomes: What Can Non-profit Employers Do?

Abstract: Engagement is a positive psychological state that is linked with a range of beneficial individual and organizational outcomes. However, the factors associated with volunteer engagement have rarely been examined. Data from 1064 volunteers of a wildlife charity in the United Kingdom revealed that both task and emotion-oriented organizational support were positively related to volunteer engagement, and volunteer engagement was positively related to volunteer happiness and perceived social worth and negatively rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 68 publications
5
78
0
Order By: Relevance
“…HR practices can be vital tools for mitigating turnover in the context of paid employees. To date, we do not fully understand the mechanism between HR practices and volunteer turnover (Alfes, Shantz, et al, ); this paper, therefore, provides an important step toward this endeavor. Our findings show that HR practices play an essential role in volunteer retention; consequently, this study contributes to existing literature and research in multiple ways.…”
Section: Discussion and Contributionsmentioning
confidence: 95%
See 1 more Smart Citation
“…HR practices can be vital tools for mitigating turnover in the context of paid employees. To date, we do not fully understand the mechanism between HR practices and volunteer turnover (Alfes, Shantz, et al, ); this paper, therefore, provides an important step toward this endeavor. Our findings show that HR practices play an essential role in volunteer retention; consequently, this study contributes to existing literature and research in multiple ways.…”
Section: Discussion and Contributionsmentioning
confidence: 95%
“…Aside from individual volunteer motives and dispositions, effective management within the organization also contributes to volunteer retention (Gazley, ; Hager & Brudney, ). Scholars have also examined volunteers' perceptions of the organizational context impacting retention success such as organizational climate (Nencini et al, ), the design of volunteer roles (Alfes, Shantz, & Saksida, ), organizational support (Alfes, Shantz, & Bailey, ), and job resources (Presti, ). Rather than relying on individual perceptions of volunteer management practices, this study builds on these findings and adopts a management perspective by drawing on objective measures of human resource (HR) practices that impact volunteer retention.…”
Section: Background and Significancementioning
confidence: 99%
“…Assumedly decoupled from the market logic, volunteer work is seen to celebrate the ideals of work autonomy, free choice, community, and social impact (Cnaan et al, ; Kelemen et al, ). Moreover, volunteer work constitutes an important site for identity work (Alfes et al, ; Cunningham, ; Grönlund, ), as it allows individuals to pursue altruistic values and political positions (Chen et al, ; Clary et al, ; Wilson, ). Furthermore, research points out how volunteering can satisfy individuals’ needs for social interaction and belonging (Hustinx and Lammertyn, ; O’Toole and Grey, ; Prouteau and Wolff, ; Wilderom and Miner, ).…”
Section: Meaningful Volunteer Workmentioning
confidence: 99%
“…Heritage volunteers may adopt a wide range of different roles and have different patterns of attendance; they also bring different previous experience and skill sets to their role. Partly as the result of the non-contractual nature of their roles, managers and researchers have sought other ways to develop commitment (Alfes, et al, 2016) and retention (Garner and Garner, 2011), and have identified the pivotal role of volunteer engagement.…”
Section: Discussionmentioning
confidence: 99%